Analisis Struktur Anatomi Batang Anyelir (Dianthus caryophyllus L.) dan Kontribusinya Terhadap Sistematik Ordo Caryophyllales - Emilia Juliyanti Bria (Fakultas Pertanian, Universitas Timor, 2018)
Caryophyllales is known as an order that has anomaly secondary growth. The anatomy of the carnation stem (Dianthus caryophyllus L.) was analyzed to obtain valid data on relationships with other family members. The primary structure of the stem, consists of epidermis composed of a layer of cells; cortex and pith are composed of parenchymal cells and have intercellular space; and the primary vascular tissue composed of the fingers consists of several tracheas of xylem, where the xylem is located on the inside and the phloem on the outside. Furthermore, in secondary growth, the stem has a normal structure with abnormal cambium activity. This is included in the characteristics of plants that have anomaly secondary growth. The results of this study can be used as a limiting character to strengthen the relationship between taxon, especially in the higher category